2016
DOI: 10.1111/cen.13136
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism and pregnancy loss: comparison with hyperthyroidism and diabetes in a Danish population‐based study

Abstract: Hypothyroidism increased the risk of both early and late pregnancy loss as did hyperthyroidism and in particular diabetes. We hypothesize that undetected or insufficiently treated maternal disease in the pregnancy may be of causal importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…Previous studies have shown that untreated or even partially treated overt hyperthyroidism during pregnancy could increase the risk of pregnancy loss and fetal mortality [ 3 , 4 ]. Women diagnosed with hyperthyroidism should counsel the endocrinologist regarding plans for pregnancy and the adverse effects of both antithyroid drugs and LT4 during pregnancy [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that untreated or even partially treated overt hyperthyroidism during pregnancy could increase the risk of pregnancy loss and fetal mortality [ 3 , 4 ]. Women diagnosed with hyperthyroidism should counsel the endocrinologist regarding plans for pregnancy and the adverse effects of both antithyroid drugs and LT4 during pregnancy [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ICD-8 codes were used to encode the diseases until 1994 when the ICD-10 codes were introduced. The following ICD codes were used to identify the main or auxiliary diagnosis of hypothyroidism (243.99-244.09 in ICD-8 codes; or E03 and E89.0 in ICD-10 codes) (25).…”
Section: Identification Of Maternal Hypothyroidismmentioning
confidence: 99%
“…The main causes of hypothyroidism in pregnant women pertain to iodine deficiency and chronic lymphocytic Hashimoto's thyroiditis. Underlying hypothyroidism is also thyroidectomy, subtotal thyroidectomy, congenital hypothyroidism [2,5]. In the prenatal period, the function of thyroid is essentially modified.…”
Section: Introductionmentioning
confidence: 99%